التخطيط الحضري والتصميم العمراني الحديث للحد من الجريمة - دراسة في جغرافية التخطيط الحضري - قلية, منصور علي (Al-Qurtas, 2026)
التخطيط الحضري والتصميم العمراني الحديث للحد من الجريمة - دراسة في جغرافية التخطيط الحضري